Temperature and convection velocities in two-component liquid droplet until micro-explosion; Experimental Thermal and Fluid Science; Vol. 109 - Antonov D. V. Dmitry Vladimirovich; Kuznetsov G. V. Geny Vladimirovich; Misyura S. Ya. Sergey Yakovlevich; Strizhak P. A. Pavel Alexandrovich (2019, 2019)
Title screen